THE ROLE OF CLASS MANAGEMENT IN IMPROVING STUDENT LEARNING ACHIEVEMENT AT SD INPRES 1 TOBOLI UTARA PARIGI DISTRICT - Rizal Rizal; Miki Risnawati (Universitas Tadulako, 2020)
The purpose of this study was to determine the role of teachers in implementing Class Management to Improve Student Achievement in SD Inpres 1 Toboli Utara Parigi District. The results of this study indicate that the implementation of classroom management or classroom management carried out by the teacher is optimal, such as: the teacher before starting the learning activities make preparations first, before carrying out the teacher's learning, first condition the class so that learning takes place more effectively, before starting the learning the teacher has prepared the device first learning such as lesson plans, syllabus and others, the teacher before carrying out learning first provides motivation or reinforcement to students, the teacher before carrying out learning first checks the presence of students, before carrying out the learning process the teacher tells students to pray first, the teacher has created and maintain the atmosphere and classroom conditions in the course of the learning process, the teacher has encouraged students to study hard and diligently to achieve learning activities and teachers carry out supervision of students in progress its learning activities.